Promosi Cyber Film Bumi Manusia - Safa Safa; Eko Harry Susanto (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
Promotion in the cyber world today, if it is connected with the film industry becomes an interesting aspect to be understood and researched as part of advertising communication activities. One of the local films that successfully attracted the attention of the audience, and the author to do research is the Earth Human Film adapted from the novel titled the same as the film by the leading Indonesian literary writer, the well-known controversy, namely Pramoedya Ananta Toer. How did the promotion of cyber film human earth produced by Frederica from Falcon Pictures Production House succeeded in gaining an audience of 1,296,714 people in less than 1 (one) month since its initial airing released. This study uses the promotion mix theory (promotional mix) by G. Belch and M. Belch, with 6 basic elements namely advertising, direct marketing, internet marketing, sales promotion, publication, and personal selling. The results showed the dominant Falcon Pictures using internet marketing, advertising and publications, and chose not to use personal selling to promote human earth films. Suggestion The writer needs to explore the application to increase the number of movie sales and improvise the film's storyline to expand the audience segmentation.Promosi di dunia cyber saat ini, jika dihubungkan dengan industri perfilman menjadi satu aspek yang menarik untuk dimengerti dan diteliti sebagai bagian dari aktivitas komunikasi periklanan. Salah satu film lokal yang sukses menarik perhatian audiens dan Penulis untuk melakukan penelitian adalah Film Bumi Manusia yang diadaptasi dari Novel berjudul sama dengan filmnya, hasil karya sastrawan terkemuka Indonesia yang terkenal sekaligus kontroversial yaitu Pramoedya Ananta Toer. Dengan menggunakan metode kualitatif, Peneliti menguraikan bagaimana Promosi Cyber Film Bumi Manusia yang diproduseri oleh Frederica dari Rumah Produksi Falcon Pictures ini berhasil mendapatkan perolehan penonton sebesar 1.296.714 orang dalam waktu kurang dari 1 (satu) bulan sejak rilis tayang perdana. Penelitian ini menggunakan teori bauran promosi (promotional mix) oleh G. Belch dan M. Belch, dengan 6 elemen dasar yaitu iklan, direct marketing, internet marketing, promosi penjualan, publikasi, dan personal selling. Hasil penelitian menunjukkan Falcon Pictures dominan menggunakan internet marketing, beriklan dan publikasi, serta memilih untuk tidak menggunakan personal selling untuk promosi Film Bumi Manusia. Saran Penulis perlu adanya eksplorasi publikasi untuk menaikkan angka penjualan film dan improvisasi alur cerita film guna memperluas segmentasi penonton.